Effect of rolling massage and ST-18 acupressure on breast milk production and decrease in fundal height - Sri Rahayu; Umaroh Umaroh (Alma Ata University Press, 2022)
Background: Breast milk production and secretion are affected by the prolactin reflex and let-down reflex. One of the problems to increase breast milk production is by rolling massage and ST-18 acupressure. ST-18 point (Ru Gen) is located lateral to the breast, 4 fingers below the nipple, and can increase blood circulation which can stimulate the alveolus to contract so that breast milk is secreted towards the nipple A previous study stated that postpartum mothers were given puerperal exercise and acupressure on the second, fourth, and seventh days after giving birth both increased milk production, but the acupressure group was higher than the postpartum exercise groupObjectives: The purpose of this study was to determine the effect of rolling massage and ST-18 acupressure on breast milk production and fundal height decrease of postpartum women.Methods: This study was an quasi experimental study. The study design was Randomized Control Group with Pre-Test and Post-Test. The population were all postpartum women in the Community Health Centers in Semarang who were assigned to 16 respondents in the treatment group and 16 respondents in the control group, collected by cluster random sampling. After obtaining consent from the respondents, the researchers began to make the pre-test on the fundal height and breast milk production in the treatment group and the control group, then post-test after 3 days of treatment. Data were analyzed by Independent t test and Mann Whitney test.Results: Characteristics of respondents in both groups showed that most of respondents aged 27.9 years, were primiparous women and had good nutritional status. The mean of increase in breast milk production were assessed from infant weight gain before and after treatment from 3117.8 grams to 3254 grams. There was a difference in breast milk production in the treatment and control group with the p value of 0.0001, and there was no difference in the decrease in fundal height in the two groups (p value=3.91), however the decrease in fundal height in the treatment group was faster than the control group which was 3.91 cm.Conclusions: The need for midwives to provide midwifery care to postpartum women in a holistic and comprehensive manner, for example in the form of rolling massage and acupressure on ST-18 point.